JOB DESIGN DURING AND REDESIGNING AFTER COVID-19 IN HOSPITALITY INDUSTRY: A CRITICAL REVIEW (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The outbreak of COVID-19, caused different changes to different industries.  Hospitality industry hit and caused different changes in operational management, from traditional operational system to immediately adapting to digitalization. The critical review paper intends to review about the job design during and redesigning after COVID-19 in hospitality industry.   ProQuest Database and Google scholar were used as searching engine to extract scholarly materials. 35 scholarly materials were obtained, after filtering remained 14, relevant scholarly materials that were analysed. The findings show that Health, Safety Protocols, Hybrid Roles and Remote Work were job design used during the period of COVID-19, while during the post-COVID-19 job redesigned strategies adopted by hotel managers; Focus on Employee Well-being, Enhanced Training, promoting trustiness and Upskilling, Technology Integration, Employee engagement, Flexibility and Adaptability. During the time of transition more attention is needed by the job designers so that to help the employees to get heel from the calamities that made them to be affected psychologically, socially and financially. This review study intends to make two contributions; First, the impacts of COVID-19 on job designing represents academic trends. Second, the review contributes to psychological pre-information to employees about the dynamic designing of their job.
Keywords: Job design; Hospitality industry; Pandemic; COVID-19